On skew version of reversible rings. - Pourtaherian, Hamideh; Sattarovich, Rakhimov Isamiddin (Academic Publications, 2011)
The paper deals with -reversible rings and their relationships with well known -symmetric, -Armendariz and -semicommutative rings. We consider a skew version of some classes of rings with respect to a ring endomorphism.